Mesenchymal Stem Cells Alleviate DHEA-Induced Polycystic Ovary Syndrome (PCOS) by Inhibiting Inflammation in Mice - Qi Xie; XingLiang Xiong; Na Xiao; Ke He; Maosheng Chen; Jing Peng; Xian Su; Hua Mei; Yanni Dai; Dan Wei; Ge Lin; Lamei Cheng (Stem Cells International)
Polycystic ovary syndrome (PCOS) is the most common cause of anovulatory infertility in women of reproductive age. Chronic inflammation is considered to be the cause of ovarian dysfunction. Increasing evidence in animal studies and in preliminary clinical trials has demonstrated that MSCs possess immunomodulatory effects via their interaction with immune cells. However, their contribution to PCOS remains unclear. In this study, we showed that the administration of hUC-MSCs could efficiently improve the pathological changes of PCOS mice induced by dehydroepiandrosterone (DHEA), including ovarian histopathology and function. Moreover, we found that the administration of MSCs significantly downregulated the expression of proinflammatory factors (TNF-α, IL-1β, and IFN-γ) and fibrosis-related genes (CTGF) in ovarian and uterus tissues and affected the systemic inflammatory response. The percentage of peripheral neutrophils, M1 macrophages, and B cells was significantly reduced, while M2 macrophages and regulatory T cells (Tregs) were increased in hUC-MSC-treated mice. In the spleen, the percentage of neutrophils, M1 macrophages, IFN-γ+CD19+B cell, IFN-γ+CD4+T cells (Th1), and IL-17+CD4+T cells (Th17) was significantly decreased in hUC-MSC-treated mice. These results suggested that hUC-MSC treatment could alleviate ovarian dysfunction by inhibiting ovarian local and systemic inflammatory responses.